1954
DOI: 10.1021/j150519a022
|View full text |Cite
|
Sign up to set email alerts
|

Ethane Hydrogenation-Cracking on Iron Catalysts with and without Alkali

Abstract: The kinetics of the hydro-cracking of ethane on iron catalysts with and without alkali additions have been studied. A general expression of the form -d [C~He]/dt = k p r~.~a p s~z has been obtained. The exponent T is 1 or a fraction; s changes from negative t o positive as potash is added to fused iron oxides, containing traces of acidic impurities, from which the catalysts were prepared by reduct,ion. A general formulation of the reaction kinetics is presented to include all the data here recorded and earlier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

1972
1972
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(69 citation statements)
references
References 0 publications
6
63
0
Order By: Relevance
“…Particular attention must be given to the interpretation of the results obtained on various transition metals [28,31]. Use was made of the kinetic analysis proposed in 1954 by Cimino et al [32] for iron catalysts, and the rate determining step was assumed to be identical on all metals where the experimental order with respect to hydrogen is negative. In 1974, Frennet et al [33] suggested an alternative to this already well accepted interpretation.…”
Section: Exchange Reactions Where C-c Bond Ruptures Are Involved In Amentioning
confidence: 99%
“…Particular attention must be given to the interpretation of the results obtained on various transition metals [28,31]. Use was made of the kinetic analysis proposed in 1954 by Cimino et al [32] for iron catalysts, and the rate determining step was assumed to be identical on all metals where the experimental order with respect to hydrogen is negative. In 1974, Frennet et al [33] suggested an alternative to this already well accepted interpretation.…”
Section: Exchange Reactions Where C-c Bond Ruptures Are Involved In Amentioning
confidence: 99%
“…The reactions are catalyzed by various transition metals. The simplest example is the reaction of ethane with hydrogen to yield methane, the kinetics of which were investigated originally on nickel (Morikawa et al, 1936), and subsequently on cobalt (Taylor and Taylor, 1939) and iron (Cimino et al, 1954). More recently, studies of the kinetics of ethane hydrogenolysis have been extended to platinum (Sinfelt, 1964b;Sinfelt et al, 1965), other Group VIII noble metals (Sinfelt and Yates, 1967;, and rhenium (Yates and Sinfelt, 1969).…”
Section: Hydrogenolysismentioning
confidence: 99%
“…The presence of hydrogenolysis products, C1 and C2, were only patent in Ni monometallic catalyst and even in the bimetallic catalyst with higher content of nickel (0.75Ni0.25Pt). It is well documented by many authors in a wide variety of studies that hydrogenolysis of alkanes on Ni-containing catalysts occurs mainly at terminal carboncarbon bonds [23][24][25][26][27][28], evidencing the presence of light alkanes. Figures 5-8 show for all catalysts used the monobranched and multibranched selectivity, respectively, as a function of the n-octane conversion.…”
Section: Hydroisomerization Of N-octanementioning
confidence: 99%